Detection of biofilm formation in Staphylococci spp. Multiple antibiotic resistance isolated from different clinical infections (Journal of the College of Basic Education, 2022)
The current study aimed to investigate the biofilm formation in isolates of Staphylococcus aureus bacteria that are resistant to multiple antibiotics, especially beta-lactams, and isolated from various clinical sources, including (burn swabs, wound swabs, ear swabs, urine samples and oropharyngeal swabs). 12 isolates were obtained. 6 of them belonged to S.aureus bacteria and the other 6 belonged to S.epidermidis bacteria, diagnosed in the laboratory, and the diagnosis was confirmed using the Vitek 2 compact system device in the bacteriology laboratory in Baquba Teaching Hospital.A sensitivity test was conducted for six antibiotics using the Kerby-Bauer method, the isolates showed varying resistance to antibiotics, and the resistance of S. aureus isolates to these